1995
DOI: 10.1002/1097-0142(19950901)76:5<853::aid-cncr2820760520>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities involving 11q13 are associated with poor prognosis in patients with squamous cell carcinoma of the head and neck

Abstract: Background. In individual patients with squamous cell carcinoma of the head and neck (SCCHN), established prognostic factors do not satisfactorily predict clinical outcome. Although the karyotype is an independent prognostic factor in certain hematologic malignancies and solid tumors, no data have been reported concerning the possible relationship between chromosomal abnormalities and clinical outcome in patients with SCCHN. Methods. In 116 cases of primary SCCHN, short term cultures were analyzed cytogenetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 23 publications
4
74
1
4
Order By: Relevance
“…Unlike Bockmühl et al (2000), no association between gain of 11q13 and reduced survival was identified; however, when tumours demonstrating amplification of this region were analysed separately a strong association with reduced disease-free survival was revealed. This association with 11q13 amplification and poor prognosis is consistent with previous classical karyotypic data (Akervall et al, 1995;Meredith et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike Bockmühl et al (2000), no association between gain of 11q13 and reduced survival was identified; however, when tumours demonstrating amplification of this region were analysed separately a strong association with reduced disease-free survival was revealed. This association with 11q13 amplification and poor prognosis is consistent with previous classical karyotypic data (Akervall et al, 1995;Meredith et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…The most widely reported aberration demonstrating a correlation with clinical outcome is amplification of chromosome 11q13. Both the amplification of this band and overexpression of the cyclin D1 oncogene have been repeatedly associated with poor prognosis (Akervall et al, 1995;Meredith et al, 1995). Many of the limitations of conventional cytogenetic analysis have been overcome with the development of molecular techniques including FISH and comparative genomic hybridisation (CGH).…”
mentioning
confidence: 99%
“…Chromosome 11q13 gains have repeatedly been reported to be associated with bad prognosis in HNSCC. 18,19 The main candidate gene is the cycD1 proto-oncogene which drives the cell from the G1 into the S phase of the cell cycle. However, overexpression of this gene seems to be an independent prognostic factor because it is not strictly related to gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Moreover, 11q13 amplification occurs in upto 20% of other carcinomas including those of the breast, bladder and pancreas, 4 and is associated with poor prognosis. 5 It is clear that the long arm of chromosme 11 harbours a cluster of oncogenes. The genes within 11q13 could serve as prognostic markers as well as therapeutic targets, so there will be a benefit derived from understanding the biology associated with the amplified genes.…”
Section: Introductionmentioning
confidence: 99%